2016
DOI: 10.13005/bbra/2027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Panax Ginseng Alcoholic Extract on Histomorphometric Changes of Ovaries in Offspring Rats from Diabetic Mothers

Abstract: Diabetes mellitus is one of the most common diseases of the body's endocrine system; and despite great progresses in its controlling in pregnant women the risk of birth of abnormal babies in these patients is significantly higher than healthy people. Now, the original and effective treatment of diabetes is consumption of insulin and glucose-lowering chemical medicines. But, these compounds have numerous side effects. According to this, consumption of medicinal plants in order to reduce the complications of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Zare et al . reported elevation of both numbers and size of primordial follicles in ovaries of three-month-old female rat infants born to diabetic mothers, which was treated with ginseng extract [ 22 ]. A recent study has reported the disappearance of ovarian cysts after a 14-day oral regimen of Korean red ginseng extract in an animal model [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zare et al . reported elevation of both numbers and size of primordial follicles in ovaries of three-month-old female rat infants born to diabetic mothers, which was treated with ginseng extract [ 22 ]. A recent study has reported the disappearance of ovarian cysts after a 14-day oral regimen of Korean red ginseng extract in an animal model [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ginseng is a powerful phytoestrogen with high antioxidant properties. There are various reports about the beneficial effects of ginseng on various disorders of the systems such as cardiovascular, endocrine, immune system, menopausal symptoms, and reproduction [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%